ANALISIS SITIRAN TESIS PASCASARJANA INSTITUT PERTANIAN BOGOR PROGRAM MAGISTER TEKNOLOGI INFORMASI UNTUK PERPUSTAKAAN TAHUN LULUS 2008-2018 - Azizah Azizah (Perpustakaan Nasional RI, 2019)
This study examines research behavior of candidate graduates of the Information Technology Masters Program for the Library (MTIP), Department of Computer Science, Bogor Agricultural University which deals with scientific communication among researchers. This study aims to determine the citation pattern of the scientific work of S2 MTIP IPB students. The thesis of MTIP IPB students examined from 2008 to 2018 totaled 66 theses of MTIP IPB students. Analysis was carried out on: the amount of literature, language, types of documents, and obsolescence of the cited literature. This study uses a descriptive analytical method with a quantitative approach through the method of taking documentation and observation data. Analysis of descriptive statistical data using percentages, mode and median. The data analyzed is the bibliography in each thesis of prospective graduates of MTIP. The number of articles cited for 10 years is 2 039 titles with an average of each citation thesis as much as 31 literature. The most cited literary language is English literature with a ratio of 53% in English and 47% in Indonesian. The most cited types of literature are books, namely 37.49%, journal articles at 26.68%, internet articles (web) at 18.92%, gray literature as much as 2.41%, proceedings as much as 2.21% and types other literature as much as 12.29. Citation of literature which has a time span of 0-10 years is 1445 (70.87%). The author with the most cited number is Sulistyo-Basuki which is 38 citations. The life cycle of the cited literature is 7 (seven) years.